2017
DOI: 10.1155/2017/4218254
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells in the Orchestration of Chronic Inflammatory Diseases

Abstract: Inflammation, altered immune cell phenotype, and functions are key features shared by diverse chronic diseases, including cardiovascular, neurodegenerative diseases, diabetes, metabolic syndrome, and cancer. Natural killer cells are innate lymphoid cells primarily involved in the immune system response to non-self-components but their plasticity is largely influenced by the pathological microenvironment. Altered NK phenotype and function have been reported in several pathological conditions, basically related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 106 publications
1
37
0
Order By: Relevance
“…However, a previous non-randomised trial suggested that mindfulness training increases NK cell activity among women recently diagnosed with breast cancer 30 , and lower levels of NK activity were detected among healthy individuals who were more distressed than their peers 8,56 . www.nature.com/scientificreports www.nature.com/scientificreports/ NK cells play a major role in the rejection of both tumour and virally infected cells; higher levels may indicate a stronger defence against these threats but the functional implications for chronic tissue inflammation are still unclear 57,58 . In any case, despite the methodological strengths of our randomised design (mainly the minimization of confounding effects), a larger trial will be required to clarify the effect of mindfulness training on the proportion of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous non-randomised trial suggested that mindfulness training increases NK cell activity among women recently diagnosed with breast cancer 30 , and lower levels of NK activity were detected among healthy individuals who were more distressed than their peers 8,56 . www.nature.com/scientificreports www.nature.com/scientificreports/ NK cells play a major role in the rejection of both tumour and virally infected cells; higher levels may indicate a stronger defence against these threats but the functional implications for chronic tissue inflammation are still unclear 57,58 . In any case, despite the methodological strengths of our randomised design (mainly the minimization of confounding effects), a larger trial will be required to clarify the effect of mindfulness training on the proportion of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…11 Of note, NK cells, particularly CD56 bright NK cells, accumulate within atherosclerotic lesions 12 and people with unstable coronary artery disease have fewer CD56 dim NK cells. 13 CD56 bright NK cells may contribute to atherosclerosis through IFN-c production, which can promote matrix metalloproteinase secretion and smooth muscle breakdown. 13 As people with HIV have increased risk of cardiovascular disease, 14 understanding the evolution of NK cell populations during HIV-1 infection is particularly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…13 CD56 bright NK cells may contribute to atherosclerosis through IFN-c production, which can promote matrix metalloproteinase secretion and smooth muscle breakdown. 13 As people with HIV have increased risk of cardiovascular disease, 14 understanding the evolution of NK cell populations during HIV-1 infection is particularly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Predominant population of NK cells is CD56 dim CD16 + and exhibits moderate expression of CD56. Approximately 5% of all NK cells show CD56 bright CD16 − phenotype and exhibit high expression of CD56 [77].…”
Section: Natural Killer Cellsmentioning
confidence: 99%